Highly efficient removal of trace thallium from contaminated source waters with ferrate: Role of in situ formed ferric nanoparticle. (1st November 2017) - Liu, Yulei; Wang, Lu; Wang, Xianshi; Huang, Zhuangsong; Xu, Chengbiao; Yang, Tao; Zhao, Xiaodan; Qi, Jingyao; Ma, Jun
Abstract: Thallium (Tl) is highly toxic to mammals and relevant pollution cases are increasing world-widely. Convenient and efficient method for the removal of trace Tl from contaminated source water is imperative. Here, the removal of trace Tl by K2 FeO4 [Fe(VI)] was investigated for the first time, with the exploration of reaction mechanisms. Six different types of water treatment agents (powdered activated carbon, Al2 (SO4 )3, FeCl3, δ-MnO2, MnO2 nano-particles, and K2 FeO4 ) were used for the removal of Tl in spiked river water, and K2 FeO4 showed excellent removal performance. Over 92% of Tl (1 μg/L) was removed within 5 min by applying 2.5 mg/L of K2 FeO4 (pH 7.0, 20 °C). XPS analysis revealed that in the reaction of Tl(I) with K2 FeO4, Tl(I) was oxidized to Tl(III), and removed by the K2 FeO4 reduced ferric particles. The removal of Tl by in situ formed and ex situ formed ferric particle was examined respectively, and the results revealed that the removal of trace Tl could be attributed to the combination of adsorption and coprecipitation processes. The hydrodynamic size of the reduced particle from K2 FeO4 ranged from 10 nm to 100 nm, and its surface was negatively charged under neutral pH condition. These factors were conducive for the efficient removal of Tl by K2 FeO4 . The effects of solution pH, coexisting ions (Na +, Ca 2+, and HCO3 − ), humic acid, solution temperature, and reductive environment on the removal and desorption of Tl were investigated, and the elimination of Tl in polluted river water and reservoir water was performed. These results suggest that K2 FeO4 could be an efficient and convenient agent on trace Tl removal. Graphical abstract: Highlights: Trace level of Tl (<1 μg/L) in source waters was removed by K2 FeO4 . Over 92% of Tl was removed within 5 min by 2.5 mg/L of K2 FeO4 . Both adsorption and coprecipitation processes were functioned on Tl removal. The adsorbed Tl was hard to be desorpted.